Elymus athericus encroachment in Wadden Sea salt marshes is driven by surface elevation change. Issue 3 (22nd June 2019) - Nolte, Stefanie; Wanner, Antonia; Stock, Martin; Jensen, Kai
Abstract: Questions: What are the main drivers of vegetation succession and the encroachment of Elymus athericus (Link) Kerguélen in ungrazed Wadden Sea salt marshes? Is (a) elevation, a proxy for tidal inundation and thus abiotic conditions, limiting the expanse of Elymus . Does sedimentation increase the spread of Elymus by (b) leading to surface elevation change or does it (c) add nitrogen and thereby allows Elymus to grow in lower elevation? Location: Salt marsh at Sönke‐Nissen‐Koog, Wadden Sea National Park Schleswig‐Holstein, Germany. Methods: The experiment was established in 2007 in the high marsh and consisted of four blocks of 12 m × 8 m. The blocks differed in surface elevation change during the experiment. Each block was subdivided into 24 plots of 1 m × 1 m. The original elevation of all plots in relation to the German ordnance datum (NHN) was assessed at the start of the experiment. Plots within the blocks were randomly assigned to one of the three N fertilization treatments. Within each plot we planted five randomly chosen individuals of Elymus . After four years of treatment, the vegetation composition and cover were recorded in all plots and aboveground biomass was collected. Results: Original elevation was found to be a main driver of succession favouring Elymus and other late‐successional plants. There was no effect of N fertilization, but a positive effect of surface elevation change on Elymus cover was detected. Conclusions: We can conclude that the positive effect of surface elevation change on Elymus is based on the resulting higher elevation and more favourable abiotic conditions caused by sedimentation, but not by the addition of nitrogen with the freshly deposited sediment. This case, therefore, is an example for an ecosystem in which encroachment is driven by a natural factor, rather than anthropogenic eutrophication. Abstract : In a field experiment, we found elevation to be the main driver of the encroachment of Elymus athericus in salt marshes. No effect of N fertilization, but a positive effect of surface elevation change on Elymus was detected. We conclude that sedimentation leads to surface elevation change and causes more favourable abiotic conditions, but does not benefit Elymus through nitrogen input.